Consequences of Delayed Dental Extraction in Lesch‐Nyhan Disease - Goodman, Emily M. (Mov Disord Clin Pract, 2014)
Patients with Lesch‐Nyhan disease (LND) often engage in self‐injurious biting. This problem requires difficult management choices, sometimes including removal of the teeth. Although many health care professionals are reluctant to remove teeth in a child because of the permanent negative cosmetic consequences of the edentulous state, disfigurement of the face and tongue from self‐biting can be worse. We analyzed the records of 5 LND patients who used mouth guards to spare the teeth. Success was variable, and dental extraction ultimately was required in 4 cases. We also reviewed previously published cases on the use of dental devices to spare teeth in LND. Various devices have been recommended, but failure rates are high, and tooth extraction often is still needed. Although dental extraction is not required in all cases, it should not be delayed when biting is severe.